Diabetes and heart failure associations in women and men: Results from the MORGAM consortium - Chadalavada, Sucharitha; Reinikainen, Jaakko; Andersson, Jonas; Di Castelnuovo, Augusto; Iacoviello, Licia; Jousilahti, Pekka; Kårhus, Line Lund; Linneberg, Allan; Söderberg, Stefan; Tunstall-Pedoe, Hugh; Lekadir, Karim; Aung, Nay; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Diabetes and its cardiovascular complications are a growing concern worldwide. Recently, some studies have demonstrated that relative risk of heart failure (HF) is higher in women with type 1 diabetes (T1DM) than in men. This study aims to validate these findings in cohorts representing five countries across Europe. Methods This study includes 88,559 (51.8% women) participants, 3,281 (46.3% women) of whom had diabetes at baseline. Survival analysis was performed with the outcomes of interest being death and HF with a follow-up time of 12 years. Sub-group analysis according to sex and type of diabetes was also performed for the HF outcome. Results 6,460 deaths were recorded, of which 567 were amongst those with diabetes. Additionally, HF was diagnosed in 2,772 individuals (446 with diabetes). A multivariable Cox proportional hazard analysis showed that there was an increased risk of death and HF (hazard ratio (HR) of 1.73 [1.58–1.89] and 2.12 [1.91–2.36], respectively) when comparing those with diabetes and those without. The HR for HF was 6.72 [2.75–16.41] for women with T1DM vs 5.80 [2.72–12.37] for men with T1DM, but the interaction term for sex differences was insignificant (p for interaction 0.45). There was no significant difference in the relative risk of HF between men and women when both types of diabetes were combined (HR 2.22 [1.93–2.54] vs 1.99 [1.67–2.38] respectively, p for interaction 0.80). Conclusion Diabetes is associated with increased risks of death and heart failure, and there was no difference in relative risk according to sex.